Effiency of Low Water Demanding Cements and Their Prospects (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The industries in Uzbekistan is developing with great factors, so that their diversity is increasing, and new modern technological methods are being introduced, as well as innovative technological systems are being put into operation. Therefore, solving problems related to production based on high-quality, cheap local raw materials and industrial waste has been one of the main tasks. One of the important areas of increasing the efficiency of social production in the current conditions of rapid development is economising. Economical use of all local resources and industrial waste, use of existing capacity and energy-efficient modern equipment, ensuring the implementation of measures such as localization of production depend to a large extent on economy. Especially, cement can be example of that. One of the most important tasks of the cement production industry is to produce high-quality, low-cost binders using local raw materials widely, to improve the quality of the development of the production of various materials, products and structures based on them, and to reduce the cost of construction, while at the same time stable production and It is important to increase the technical and economic indicators of the production of ecologically clean, local raw materials, effective materials from secondary waste, to improve the durability of the produced materials, and to be used in the construction industry in the territory of the republic.